What will be the future of dinoprostone in labor induction?. Issue 3 (26th January 2022) - Ragusa, Antonio; De Luca, Caterina; Zucchelli, Emma; Svelato, Alessandro
Abstract : A productive debate is needed about the use of dinoprostone in labor induction.